Perbedaan Gizi pada Bayi: Membandingkan Profil Karbohidrat dan Lipid Antara Bayi dengan Status Gizi Normal dan Obesitas - Ria Puspitasari; Nur Aisiyah Widjaja; Eva Ardianah; Tutfah Razzak Fitriari (Universitas Airlangga, 2024)
Background: For supporting the infant’s growth and development, Human Milk (HM) is the most suitable nutritional source, especially during 6 months. Growth study showed different growth between breastfed infants and formula-fed infants, in which they are thinner compared to formula-fed infants, but some breastfed infants are overnutrition (overweight and obese). Objective: to investigate the macronutrient content of HM in exclusive breast-feeding infants aged under 12 months old. Methods: The study’s design was a case-control, conducted on 20 lactating mothers (residents and employee) in the pediatric departemen at Regional General Hospital Dr. Soetomo Surabaya in March–April 2018. HM of the infant with overnutrition was included in the Overnutrition (ON) group, and HM of the infant with normal nutrition was included in the Normal (N) group. To obtain the HM samples, the researchers recruited lactating mothers who participated in this study voluntarily. The lactating mothers must breastfeed their infants predominantly, and their infant’s age must be less than 12 months old. The macronutrients content in HM were measured using a Human Milk Analyzer (HMA) (MIRIS®, Uppsala, Sweden). Statistical analysis conducted was test of normality (Shapiro Wilk) and test of homogeneity followed by Mann Whitney U test and Fisher exact test with the level of significance <0.05. Results: We got 20 samples of HM from 20 lactating mothers, in which ten infants were determined as overnutrition (2 were categorized as overweight and 8 were obese) and grouped in ON, while 10 infants were normal and were grouped in the N group. It was found that the ON group had higher lipid content than the N group (4.33[2.0-6.8] vs. 2.40 [1.2-3.9] g, p=0.019). Protein content was almost similar in both groups (p=0.853), The ON group had lower carbohydrate content than (2.42 [1.5-3.7] g) than the N group (3.42 [2.1-4] g), p=0.004. The ON group had higher energy content (53.85 [31.20-76.20] kcal/ml) than the N group (39.90 [26.40-51.90] kcal/ml, p=0.065). Conclusion: The incidence of overnutrition during infancy is likely affected by high lipids content in HM than other macronutrients. The carbohydrate content was significantly low in overnutrition infants.